Unveiling outcomes in coexisting severe aortic stenosis and transthyretin cardiac amyloidosis. (8th September 2020) - Rosenblum, Hannah; Masri, Ahmad; Narotsky, David L.; Goldsmith, Jeff; Hamid, Nadira; Hahn, Rebecca T.; Kodali, Susheel; Vahl, Torsten; Nazif, Tamim; Khalique, Omar K.; Bokhari, Sabahat; Soman, Prem; et al.
Abstract: Aims: Advances in diagnostic imaging have increased the recognition of coexisting transthyretin cardiac amyloidosis (ATTR‐CA) and severe aortic stenosis (AS), with a reported prevalence between 8–16%. In this prospective study, we aimed to evaluate the implications of ATTR‐CA on outcomes after transcatheter aortic valve replacement (TAVR). Methods and results: At two academic centres, we screened patients with severe AS undergoing TAVR for ATTR‐CA. Using Kaplan–Meier analysis, we compared survival free from death and a combined endpoint of death and first heart failure hospitalization between patients with and without ATTR‐CA. Cox proportional‐hazards models were used to determine the association of ATTR‐CA with these endpoints. The rate of heart failure hospitalization was compared amongst those with and without ATTR‐CA. Overall, 204 patients (83 years, 65% male, Society of Thoracic Surgeons score 6.6%, 72% New York Heart Association class III/IV) were included, 27 (13%) with ATTR‐CA. Over a median follow‐up of 2.04 years, there was no difference in mortality (log rank, P  = 0.99) or the combined endpoint (log rank, P  = 0.79) between patients with and without ATTR‐CA. In Cox proportional‐hazards models, the presence of ATTR‐CA was not associated with death. However, patients with ATTR‐CA had increased rates of heart failure hospitalization at 1 year (0.372 vs. 0.114 events/person‐year, P  < 0.004) and 3 years (0.199 vs. 0.111 events/person‐year, P  = 0.087) following TAVR. Conclusion: In moderate‐risk patients with severe AS undergoing TAVR, there was a 13% prevalence of ATTR‐CA, which did not affect mortality. The observed increase in heart failure hospitalization following TAVR in those with ATTR‐CA suggests the consequences of the underlying infiltrative myopathy.